Free Trade and Labour and Environmental Standards in MERCOSUR - María Belén Olmos Giupponi (Colombia Internacional, 2014)
The main argument put forward in the article is that MERCOSUR accommodated the protection of human rights as non-trade issues in its institutional framework, analysing the conflict between the protection of human rights and trade issues at the sub-regional level. In order to give a complete and clear picture of these developments, the paper examines member states’ constitutional provisions and the implementation of MERCOSUR labour and environmental standards before national courts.